Writing Assessment Literacy and Its Role in Shaping EFL Student Learning and Performance in Indonesian Universities - Pujiawati, Nia; Mujiyanto, Januarius; Hartono, Rudi; Yuliasri, Issy (Universitas Hamzanwadi, 2025)
Writing Assessment Literacy (WAL) is an essential competency for English lecturers in higher education, particularly in English as a Foreign Language (EFL) contexts such as Indonesia, where cultural and pedagogical traditions often shape assessment practices. Despite growing attention to assessment literacy, limited research has explored how different WAL levels relate to students’ learning experiences and writing performance. This study addresses that gap by examining how lecturers’ WAL influences student outcomes in Indonesian universities. Using a sequential mixed-methods design, Phase 1 involved 24 EFL lecturers who completed a Writing Assessment Literacy Test. Results identified three WAL groups: Excellent (50%), Good (29.2%), and Low (20.8%). One lecturer from each group was selected for Phase 2, along with their respective student cohorts (n = 66). Data sources included student responses to an Assessment Experience Questionnaire, writing samples evaluated with a standardized rubric, and statistical analyses using Kruskal-Wallis tests and Spearman rank correlations. Findings revealed significant differences in student learning experiences across groups (K = 40.791, p < 0.0001, η = 0.616), with the Low WAL group reporting the highest learning scores. In contrast, the Good WAL group achieved the highest writing performance (K = 6.531, p = 0.038, η = 0.0719), suggesting a possible “optimal zone” of assessment practice. Strong positive correlations were found between student learning and writing outcomes (ρ = 0.63–0.84, p < 0.05). These findings indicate that WAL influences student outcomes, but not in a strictly linear way, emphasizing the need for context-aware and pedagogically responsive assessment literacy development.